2006
DOI: 10.2320/matertrans.47.2882
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Thermal Stability of Cu<SUB>46.25</SUB>Zr<SUB>44.25</SUB>Al<SUB>7.5</SUB>Er<SUB>2</SUB> Bulk Metallic Glass with a Diameter of 12 mm

Abstract: Effect of substituting a small amount of Er for Zr in Cu 46:25 Zr 46:25 AI 7:5 alloy on glass-forming ability was investigated. The addition of 2 at% Er effectively improves glass formation and glassy rod with a diameter of at least 12 mm was formed by copper mold casting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recently, much attention has been paid to the Cu-Zr-based metallic glasses [7][8][9][10], due to their simple composition, innocuous and free of noble elements, large GFA, and wide composition range. Research has demonstrated that element addition and displacing is an efficient way to prepare BMG with better GFA [3,[10][11][12][13][14][15]. The ternary Cu-based BMGs were first reported in Cu-Zr-Ti and Cu-Zr-Al alloy systems by Inoue group [8,16].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, much attention has been paid to the Cu-Zr-based metallic glasses [7][8][9][10], due to their simple composition, innocuous and free of noble elements, large GFA, and wide composition range. Research has demonstrated that element addition and displacing is an efficient way to prepare BMG with better GFA [3,[10][11][12][13][14][15]. The ternary Cu-based BMGs were first reported in Cu-Zr-Ti and Cu-Zr-Al alloy systems by Inoue group [8,16].…”
Section: Introductionmentioning
confidence: 97%